Household air pollution and blood markers of inflammation: A cross‐sectional analysis. (22nd March 2021) - Fandiño‐Del‐Rio, Magdalena; Kephart, Josiah L.; Williams, Kendra N.; Malpartida, Gary; Boyd Barr, Dana; Steenland, Kyle; Koehler, Kirsten; Checkley, William
Abstract: Household air pollution (HAP) from biomass stoves is a leading risk factor for cardiopulmonary outcomes; however, its toxicity pathways and relationship with inflammation markers are poorly understood. Among 180 adult women in rural Peru, we examined the cross‐sectional exposure‐response relationship between biomass HAP and markers of inflammation in blood using baseline measurements from a randomized trial. We measured markers of inflammation (CRP, IL‐6, IL‐10, IL‐1β, and TNF‐α) with dried blood spots, 48‐h kitchen area concentrations and personal exposures to fine particulate matter (PM2.5 ), black carbon (BC), and carbon monoxide (CO), and 48‐h kitchen concentrations of nitrogen dioxide (NO2 ) in a subset of 97 participants. We conducted an exposure‐response analysis between quintiles of HAP levels and markers of inflammation. Markers of inflammation were more strongly associated with kitchen area concentrations of BC than PM2.5 . As expected, kitchen area BC concentrations were positively associated with TNF‐α (pro‐inflammatory) concentrations and negatively associated with IL‐10, an anti‐inflammatory marker, controlling for confounders in single‐ and multi‐pollutant models. However, contrary to expectations, kitchen area BC and NO2 concentrations were negatively associated with IL‐1β, a pro‐inflammatory marker. No associations were identified for IL‐6 or CRP, or for any marker in relation to personal exposures.